Lipidomics Unveils Critical Lipid Pathway Shifts in Alport Syndrome - Belen Requena; Amir Shabaka; Borja Lanzon; Sara Martinez; Isabel Galan Carrillo; Teresa Bada-Bosch; Angel Sevillano; Ana Maria Tato-Ribera; Coral Barbas; Gema Medina-Gomez; Carolina Gonzalez-Riano; Gema Fernandez-Juarez (Kidney International Reports, 2025)
Introduction: Alport syndrome (AS) is a hereditary kidney disease from COL4A3–5 pathogenic variants causing glomerular basement membrane abnormalities. Although genetic and structural aspects are known, mechanisms linking collagen IV defects to podocyte injury are unclear. Lipotoxicity and lipid dysregulation likely mediate podocyte damage in AS, similar to diabetic kidney disease (DKD). Methods: We sought to identify plasma and urine lipid alterations in autosomal dominant AS (ADAS) and X-linked AS (XLAS) compared with DKD and healthy controls. Using liquid chromatography coupled to mass spectrometry (MS), we annotated 580 and 203 lipid species in plasma and urine, respectively. Volcano plot and receiver operating characteristic (ROC) analyses (area under the curve [AUC] ≥ 0.80) were used to identify key lipids and highlight relevant lipotoxic pathways. Multivariate prediction of renal outcomes by specific lipid species was further performed. Results: Compared with controls, AS exhibited unbalanced sphingolipid (SL) catabolism, ceramide (Cer) overload, and impaired fatty acid (FA) β-oxidation, alongside phospholipid and cholesterol imbalances suggestive of compromised isoform A1 of adenosine triphosphate–binding cassette transporter (ABCA1)-mediated lipid efflux and mitochondrial dysfunction. Comparisons with DKD indicated a shared lipotoxic environment with Cer elevation and disrupted FA metabolism. However, disease-specific adaptations emerged, with severe ABCA1 dysfunction and marked phospholipid or cholesterol derangements in DKD, whereas AS showed pronounced sphingomyelin (SM) depletion. Key lipids identified included urinary hexosylceramide (HexCer) 18:0(3O)/24:0(2OH) and acylcarnitine (CAR) 12:0. These findings were supported by multivariate prediction of renal outcomes by specific lipid species. Conclusion: These findings demonstrate that AS involves distinct lipidomic disruptions and underscore shared lipotoxic mechanisms with DKD. This improved understanding of disease-specific lipid imbalances provides new potential therapeutic targets to mitigate podocyte injury and slow progression of AS.